PENERAPAN ETIKA BISNIS ISLAM DALAM TRANSAKSI JUAL BELI DI PASAR TRADISIONAL PLOSO - Lathifah, Siti Nurul; Rohman, Abdur (LPPM IAI Nazhatut Thullab, 2024)
A traditional market is a place that can bring together sellers and buyers to transact directly, providing daily needs. Traditional markets are still a common place for sales transactions in Indonesia, including the Ploso traditional market, Jombang Regency. However, unethical business practices often occur in traditional markets, such as fraud, selling fake goods, and giving consumers unfair prices. Therefore, it is necessary to apply correct business ethics and in accordance with the principles of Islamic economic ethics in carrying out sales transactions in traditional markets. This research method uses a qualitative method using data sources directly from the field, in the form of observations, interviews and documentation from several sources. The results of this research show that the majority of traders in the Ploso traditional market have implemented the principles of Islamic business ethics, such as honesty, fairness and not committing fraud in transactions. However, there are still some traders who do not fully understand and apply the principles of Islamic business ethics. Keywords : Islamic Business Ethics, Buying and Selling, Traditional Markets.